Kajian Bahasa Rupa Berdasar Rekaman Video Pergelaran Wayang Kulit Purwa dalam Lakon ’Parta Krama’ - Ismurdyahwati Ismurdyahwati; Setiawan Sabana; Primadi Primadi; Prijanto Sunarto (Journal of Visual Art and Design, 2007)
The shadow effect of leather puppet’s movements on the screen can be used to determine performance quality of the puppet and the creativity of a puppeteer. The most important tools to perform the shadows effect are blencong (traditional lamps), kelir (screen) and debog (banana tree trunk). Therefore, many of the terminologies used in this study refers to terminologies used in the puppet performance of Javanese customs, particularly Yogyakarta’s style, which originates from the School of puppet play performance of Habirandha in Yogyakarta - Indonesia. The study observed detailed ‘movement’ of Purwa in Yogyakarta’s style, as each detailed movement possesses its own story that determines the plays and body language of character in the leather puppet performance. To observe facial expression of puppet characters, the study uses the 11th sequence and 70 facial expressions (gambar) of movement in the Kedhaton Dwarawati acts. The study observes that in each “space” and “time” of plays there are stories of movement, which can be used to describe the visual language of shadow leather-puppet performance.